MENINGKATKAN HASIL PEMBELAJARAN IPS TENTANG PERKEMBANGAN TEKNOLOGI KOMUNIKASI MELALUI PENGGUNAAN PENDEKATAN SAINTIFIK - Dedeng Febriana Hakim (LPPM Universitas Perjuangan Tasikmalaya, 2021)
Abstract: The purpose of this study is to describe the use of scientific learning models in plans for implementing learning, implementing learning, and improving student learning outcomes. The research method used was Classroom Action Research (CAR). This study consisted of two cycles, each of which was conducted two meetings. Each cycle consists of four stages, namely 1) planning, 2) implementation, 3) observation / observation, and 4) reflection.The results of the study in the first cycle of preparing a learning implementation planÂ Â Â Â Â Â Â Â Â to obtain results in the pre cycle 55.83% with very less criteria. Then in cycle I obtained a value of 80.83% with good criteria and in cycle II obtained a value of 97.5 with very good criteria. Meanwhile, observations of observations of learning implementation obtained results that increased from 40% in the pre cycle, to 73, 33% in the first cycle in the